Impact of the Lockdown Due to COVID-19 Pandemic in the Use of Combined Hormonal Oral Contraception in Spain – Results of a National Survey: Encovid - Lete I; Novalbos J; de la Viuda E; Lugo F; Herrero M; Obiol M; Perelló J; Sanchez-Borrego R (Dove Medical Press, 2021)
Iñaki Lete,1 Jesus Novalbos,2 Esther de la Viuda,3 Felix Lugo,4 Mercedes Herrero,5 Marian Obiol,6 Josep Perelló,7 Rafael Sanchez-Borrego8 1Unit of Clinical Management of Obstetrics and Gynaecology, Araba University Hospital, Vitoria, Spain; 2Medical Department, Theramex SLU, Madrid, Spain; 3Gynaecology and Obstetrics Department, University Hospital of Guadalajara, Guadalajara, Spain; 4Intimate Health Unit Diatros Woman´s Clinic, Barcelona, Spain; 5Gynaecology Department Gine4, HM Hospitals, Madrid, Spain; 6Reproductive and Sexual Health Centre Fuente De San Luis, Valencia, Spain; 7Gynaecology and Obstetrics Department, Sant Pau Hospital, Barcelona, Spain; 8DIATROS, Woman’s Clinic, Barcelona, SpainCorrespondence: Iñaki LeteUnit of Clinical Management of Obstetrics and Gynaecology. Araba University Hospital, Jose Atxotegi s/n, Vitoria, 01009, SpainTel +34 945007204Email luisignacio.letelasa@osakidetza.netObjective: To know the contraceptive behaviour of Spanish women who use combined oral contraception (COC) during the period of lockdown due to COVID-19.Methods: Cross-sectional, descriptive study of a sample of Spanish women who use COC based on a survey conducted through social networks using the online platform Survey Monkey. The survey was conducted during the period of home confinement.Results: A total of 1407 women answered the survey and 937 were valid for the analysis. A total of 675 women (71.8%) were confined all day at home. During confinement 96,6% of women continued to use the COC, 53.5% responded that their sexual activity decreased during this time and 54% that their physical activity had decreased. A significant percentage of women (10.3%) recognized a worsening of premenstrual symptoms.Conclusion: Despite the lockdown and the decrease in the frequency of sexual intercourse, the Spanish women who use COC did not abandon its use during the period of time analysed.Keywords: COVID-19, confinement, combined oral contraception, discontinuation, premenstrual symptoms